A low fermentable oligo-di-mono-saccharides and polyols (FODMAP) diet is a balanced therapy for fibromyalgia with nutritional and symptomatic benefits - Marum, A.P. (2018)
Introduction: Fibromyalgia is a chronic rheumatic disease producing widespread pain, associated to a major comorbidity -irritable bowel syndrome. Low FODMAPS diet (low fermentable oligo-di-mono-saccharides and polyols diet) has been effective in controlling irritable bowel syndrome symptoms. Overweight is an aggravating factor for fi bromyalgia. We studied effects of low fermentable oligo-di-mono-saccharides and polyols diets on fi bromyalgia symptoms and weight status. Methods: A longitudinal study was performed on 38 fi bromyalgia patients using a four-week, repeated assessment as follow: M1 = first assessments/presentation of individual low fermentable oligo-di-mono-saccharides and polyols diet; M2 = second assessments/reintroduction of FODMAPs; M3 = final assessments/nutritional counselling. The assessment instruments applied were: Fibromyalgia Survey Questionnaire (FSQ); Severity Score System (IBS-SSS); visual analogic scale (VAS). Body mass-index/composition and waist circumference (WC) were also measured. Daily macro-micronutrients and FODMAP intake were quantifi ed at each moment of the study. Results: The studied cohort was 37% overweight, 34% obese (average body mass-index 27.4 ± 4.6; excess fat mass 39.4 ± 7%). Weight, body mass-index and waist circumference decreased signifi cantly (p < 0.01) with low fermentable oligo-di-mono-saccharides and polyols diet, but no signifi cant effect on body composition was observed. All fi bromyalgia symptoms, including somatic pain, declined signifi cantly post-LFD (p < 0.01); as well for severity of fi bromyalgia [Fibromyalgia survey questionnaire: M1 = 21.8; M2 = 16.9; M3 = 17.0 (p < 0.01)]. The intake of essential nutrients (fi ber, calcium, magnesium and vitamin D) showed no signifi cant difference. The signifi cant reduction in FODMAP intake (M1 = 24.4 g; M2 = 2.6g; p < 0.01) refl ected the “Diet adherence” (85%). “Satisfaction with improvement of symptoms” (76%), showed correlating with “diet adherence” (r = 0.65; p < 0.01). Conclusions: Results are highly encouraging, showing low fermentable oligo-di-mono-saccharides and polyols diets as a nutritionally balanced approach, contributing to weight loss and reducing the severity of FM fi bromyalgia symptoms.